2011
DOI: 10.1002/rcs.390
|View full text |Cite
|
Sign up to set email alerts
|

How to build patient‐specific synthetic abdominal anatomies. An innovative approach from physical toward hybrid surgical simulators

Abstract: This simulator can be used in the field of abdominal surgery to train students and as a testing environment to assess and validate innovative surgical technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 26 publications
0
58
0
Order By: Relevance
“…Similar findings have been demonstrated in abdominal surgery, as Condino et al recreated a whole abdominal cavity true to patient-specific anatomy based on imaging. 12 The key advantages were seen in the ability to plan the operation with immense accuracy, as it was patient specific and served as a better training tool than traditional simulators.…”
Section: Preoperative Planningmentioning
confidence: 99%
“…Similar findings have been demonstrated in abdominal surgery, as Condino et al recreated a whole abdominal cavity true to patient-specific anatomy based on imaging. 12 The key advantages were seen in the ability to plan the operation with immense accuracy, as it was patient specific and served as a better training tool than traditional simulators.…”
Section: Preoperative Planningmentioning
confidence: 99%
“…The tests consisted of simulating a surgical procedure using the SPRINT robot and a silicone replica of the abdominal anatomy of a real patient, embedded in a commercial mannequin [31]. Since cholecystectomy can be considered a benchmark for surgical procedures and devices [32], it was chosen as the preliminary test for our Computer Guidance Module.…”
Section: Preliminary Evaluationmentioning
confidence: 99%
“…To clarify and understand what is the best prediction for the future of the technology itself, production time of objects and costs should also be considered. Different researchers have indicated that they have found 3D printing a cost-effective technology [110][111][112]. However, some other investigators have doubted efficiency and price of RP [113].…”
Section: Prospective Visionsmentioning
confidence: 99%